Strengthening Teacher and Educational Staff Competencies and Participation in School Quality Management - Nor Azizah; Maya Madina; Widy Noviani; Aslamiah Aslamiah; Celia Cinantya (FKIP - Universitas Riau, 2026)
This study aims to analyze how principal-led leadership strategies are operationalized to strengthen teacher competencies and structure the participation of educational staff within an integrated school quality management system at SMKN 2 Marabahan. Adopting a descriptive qualitative design, data were collected through in-depth interviews, observations, and document analysis involving the principal, teachers, and educational staff selected via purposive sampling. Data analysis followed the Miles and Huberman interactive model. The findings reveal that school quality improvement is enacted through three interrelated strategic mechanisms: continuous professional development via academic supervision and internal training, competency-based task delegation aligned with institutional needs, and the cultivation of a collaborative work culture. The principal functions as the coordinating actor who aligns these strategies, while teachers serve as the main instructional agents and educational staff operate as strategic partners in administrative management, digital services, and data governance. Participation is institutionalized through regular coordination meetings, shared decision-making forums, and the structured involvement of educational staff in planning and quality assurance processes. These mechanisms contribute to increased institutional efficiency, transparency, and collective accountability. The study concludes that inclusive and integrative leadership is critical for sustainable school quality management, as it connects teacher competence development with participatory governance involving educational staff. This model is particularly relevant for vocational schools navigating the challenges of digital transformation.